Flipping the switch: tools for detecting small molecule inhibitors of staphylococcal virulence - Quave, Cassandra L.; Horswill, Alexander R. (Frontiers in Microbiology, 2014)
Through the expression of the accessory gene regulator (agr) quorum sensing cascade, S. aureus is able to produce an extensive array of enzymes, hemolysins and immunomodulators essential to its ability to spread through the host tissues and cause disease. Many have argued for the discovery and development of quorum sensing inhibitors (QSIs) to augment existing antibiotics as adjuvant therapies. Here, we discuss the state-of-the-art tools that can be used to conduct screens for the identification of such QSIs. Examples include fluorescent reporters, MS-detection of autoinducing peptide (AIP) production, agar plate methods for detection of hemolysins and lipase, HPLC-detection of hemolysins from supernatants, and cell-toxicity assays for detecting damage (or relief thereof) against human keratinocyte (HaCat) cells. In addition to providing a description of these various approaches, we also discuss their amenability to low-, medium- and high-throughput screening efforts for the identification of novel QSIs.